Isolation, Mutagenesis, and Organic Acid Secretion of a Highly Efficient Phosphate-Solubilizing Fungus - Yang, Tianyou; Li, Linbo; Wang, Baoshi; Tian, Jing; Shi, Fanghao; Zhang, Shishuang; Wu, Zhongqi (Frontiers in Microbiology, 2022)
The highly effective phosphate-solubilizing microorganisms are significant for making full use of the potential phosphorus resources in the soil and alleviating the shortage of phosphorus resources. In this study, a phosphate-solubilizing fungus was isolated from wheat and cotton rhizosphere soils in the lower reaches of the Yellow River in China and was identified as Penicillium oxalicum by morphological and ITS sequencing analysis. In order to obtain a fungus with more efficient phosphorus solubilization ability, we tested three positive mutant strains (P1, P2, P3) and three negative mutant strains (N1, N2, N3) through low-energy nitrogen ion implantation mutagenesis. Compared with the parental strain, the phosphate-solubilizing capacity of P1, P2, and P3 was enhanced by 56.88%, 42.26%, and 32.15%, respectively, and that of N1, N2, and N3 was weakened by 47.53%, 35.27%, and 30.86%, respectively. Compared with the parental strain, the total amount of organic acids secreted significantly increased in the three positive mutant strains and decreased in the negative mutant strains; the pH of culture medium was significantly lower in the positive mutant strains and higher in the negative mutant strains. The capacity of phosphate-solubilizing fungus to secrete organic acids and reduce the growth-medium pH was closely related to its phosphate-solubilizing ability. The changes in the amount of organic acids secreted by mutants can alter their acidification and phosphate-solubilizing capacity. In conclusion, this study offers a theoretical basis and strain materials for the exploration and application of phosphate-solubilizing fungi.